Facies and provenance analysis of the Midcontinent Rift System (MRS) in Kansas - Azmi, Iffat (Kansas State University, 2020)
The Midcontinent Rift System (MRS) formed a half-graben that extends into NE Kansas. The Precambrian rift succession, penetrated by Texaco Noel Poersch#1 (NP#1) well in Washington Co. at depths between 2846 and 11300 ft, comprises two successions. The lower one (11300-7429 ft) is dominated by clastic sediments and the upper one (7429-2846 ft) mainly by volcanic rocks, which suggests a radical change during rift evolution. This study is aimed at describing the sedimentary succession within the rift in Kansas, relating variations in sedimentary facies to the different stages of rift development. Detailed facies and provenance analyses were carried out in discontinuous cores retrieved from the lower and upper successions (5395-11300 ft deep). Sixteen lithofacies were identified, grouped into six different facies associations (fluvial, eolian, mudflat/lake margin, lacustrine, alluvial fan, and fan delta). Overall, the studied succession comprises continental deposits laid down dominantly in alluvial and eolian settings, with the intermittent development of lacustrine systems. Three rift sequences, bound by flooding surfaces and controlled by tectonic pulses in rift basin, were identified. Superimposed on the tectonic phases, changing climate conditions resulted in recurrent dry and wet cycles. Provenance analysis showed a higher contribution of infracrustal rocks in the source areas. Minor shifts in provenance could be due to re-arrangements of faulted block and variable proportion of axial vs. transversal input into the rift basin. Despite the tectono-stratigraphic framework typical of a syn-rift succession, based on the available geochronological and compositional data, the rift succession in KS seems to be more compatible with post-rift successions elsewhere.
Keywords: Midcontinent Rift System; Noel Poersch-1; Facies analysis; Tectonostratigrapic framework; Provenance analysis; Depositional model